Separation and reunion in modern China - Stafford, Charles (Cambridge University Press, 2000)
In this distinctive book, Charles Stafford describes the Chinese fascination with separation and reunion. Drawing on his field studies in Taiwan and mainland China, he gives a vivid account of festivals of reunion, rituals for the sending-off of gods, silent leave-takings, poetic words of parting, and bitter political rhetoric. Stafford examines how these idioms and practices help people situate themselves in historical communities, and how they are deployed in official Chinese rhetoric concerning Taiwan. The discussion of these everyday rituals offers rich insights into Chinese and Taiwanese society and culture.